PENGARUH PEMANFAATAN SUMBER BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR - Muhamad Burhan; Yon Rizal; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This study aims to determine the effect of student perceptions about the use of learning resources and motivation toward learning outcomes of Social Studies. The population in this study is a total of 326 students. Using the Slovin formula with Simple random sampling obtained a sample of 180 students. Hypotheses were analyzed using simple linear regression and multiple linear regression. Besed on the data analysis obtained the following results: (1) There is a positive and significant effect of use of learning resources on learning outcomes of Social Studies at the eighth grade students of SMP Negeri 1 Kalianda of 23.7%; (2) There is a positive and significant influence of motivation toward learning outcomes of Social Studies at the eighth grade students of SMP Negeri 1 Kalianda by 18%; (3) There is a positive and significant effect of use of learning resources and motivation toward learning outcomes of Social Studies at the eighth grade student of SMP Negeri 1 Kalianda 37.7%.Penelitian ini bertujuan untuk mengetahui pengaruh Persepsi siswa tentang pemanfaatan sumber belajar dan motivasi belajar terhadap hasil belajar IPS Terpadu. Populasi dalam penelitian ini sebanyak 326 siswa. Menggunakan rumus Slovin dengan simple random sampling diperoleh sampel sebanyak 180 siswa. Pengujian hipotesis dianalisis dengan menggunakan regresi linier sederhana dan regresi linier multipel. Berdasarkan analisis diperoleh hasil penelitian sebagai berikut: (1) Ada pengaruh positif dan signifikan pemanfaatan sumber belajar terhadap hasil belajar IPS Terpadu siswa kelas VIII SMP Negeri 1 Kalianda sebesar 23,7%; (2) Ada pengaruh positif dan signifikan motivasi belajar terhadap hasil belajar IPS Terpadu siswa kelas VIII SMP Negeri 1 Kalianda sebesar 18 %; (3) Ada pengaruh positif dan signifikan pemanfaatan sumber belajar dan motivasi belajar terhadap hasil belajar IPS Terpadu siswa kelas VIII SMP Negeri 1 Kalianda sebesar 37,7%.Kata kunci: hasil belajar, motivasi,pemanfaatan sumber belajar